Bacteriophage LDT325 enhances Pseudomonas syringae tolerance by improving antioxidant defense in tea plant [Camellia sinensis (L.) O. Kuntze] - Liu, Li; Huang, Anqi; Zhang, Hua; Li, Yubao; Wang, Lei (Frontiers in Microbiology, 2025)
Bud blight caused by Pseudomonas syringae is a serious disease affecting tea plants and causing severe damage to production output and quality. Phages play an important role in controlling the development of bacterial diseases in plants. Previous studies have shown that the tolerance of phage-treated tea plants to bud blight was notably greater compared with that of the control group. In the present study, we determined the effect of bacteriophage therapy on physiological and biochemical parameters of tea leaves. Transmission electron microscopy (TEM) was used to analyze the cellular structure of tea leaves, and bioinformatics was used to analyze the phage. Results revealed that bacteriophage treatment can enhance the expression of antioxidant enzyme genes (CsSOD, CsCAT, and CsPOD). The levels of osmotic adjustment compounds, including proline and soluble sugars, were also elevated, suggesting that bacteriophage enhances the osmotic adjustment capacity in tea plants. TEM analysis revealed that the integrity of the cell structure of the tea leaves treated with phage was notably better compared with that of the control group. Interestingly, we also observed that the phage lysed the animal pathogen Salmonella as well as the plant pathogen P. syringae. Using NCBI BLASTn to compare the entire genome with other nucleotide sequences, we found that the phage LDT325 exhibited cross-species characteristics that had not been previously reported. In summary, our findings demonstrate that bacteriophages can protect tea plants from damage caused by bacterial diseases by regulating antioxidant systems.